A pH-responsive Pt-based nanoradiosensitizer for enhanced radiotherapy via oxidative stress amplification. Issue 32 (3rd August 2021) - Yu, Licheng; Zhang, Xiaolei; Li, Xiaomin; Zhang, Zhenjie; Niu, Xiaoyan; Wang, Xiaohui; Wang, Wei; Yuan, Zhi
Abstract : This work could reduce tumor radioresistance and increase the effect of radiotherapy. Abstract : Tumor radioresistance is a major issue in radiotherapy. To address it, a pH-responsive nanoradiosensitizer was synthesized employing a simple method. Initially, chloroplatinic acid was reduced by human serum albumin (HSA) to form HSA-wrapped Pt@HSA nanoparticles (NPs). Subsequently, cinnamicaldehyde (CA) was grafted on Pt@HSA via aldimine condensation to obtain nanoradiosensitizer Pt@HSA/CA NPs. CA would be released in tumor cells (pH = 5.5) to induce the production of reactive oxygen species, including H2 O2, ˙OH, etc . The increased decomposition of H2 O2 catalyzed by the NPs resulted in enhanced production of oxygen, leading to hypoxia relief of the tumor cells, which is beneficial for radiotherapy. Due to the high X-ray attenuation coefficient of Pt, Pt@HSA/CA NPs enhance the energy deposition of radiation. Cytotoxicity assay revealed that Pt@HSA/CA NPs resulted in a cell death rate of 77%, which was 24.4% higher than that of Pt@HSA NPs even under low-dose X-ray irradiation of 4 Gy. Colony formation assay demonstrated that the sensitization enhancement ratio was 1.37, indicating that Pt@HSA/CA NPs displayed remarkable radiosensitizing ability. Notably, in vivo results indicated that the NPs could increase the tumor inhibition rate to 91.2% with negligible side effects to normal tissues. These results demonstrate that Pt@HSA/CA NPs had outstanding tumor curative efficacy and hypotoxicity.